IMPLEMENTASI SANKSI TINDAKAN BERSIFAT PRIMUM REMEDIUM TERHADAP ANAK BERKONFLIK DENGAN HUKUM - Mashuril Anwar (Cepalo, 2021)
Criminal sanctions are more popular than action sanctions at the application level. Action sanctions formulation is regulated in Articles 82 and 83 of the Juvenile Criminal Justice System Law, while criminal sanctions are the last resort. However, criminal sanctions are still the "prima donna" in law enforcement practices against children in conflict. This condition raises various problems such as the overcapacity of correctional institutions, burdens the state budget, and creates a stigma against children in conflict with the law. Because the purpose of implementing the juvenile criminal justice system is in the child's best interests, action sanctions should be prioritised, even though criminal sanctions are needed in law enforcement against children in conflict with the law. Therefore, an idea emerged to restore criminal sanctions as ultimum remedium and strengthen action sanctions as primum remedium. The problem discussed in this study is how to implement primum remedium action sanctions against children in conflict with the law? And how to strengthen primum remedium action sanctions against children in conflict with the law? This study uses a normative juridical, an empirical juridical, and a comparative methods. The data in this article are sourced from primary and secondary data processed through description, prescription, and system. The results indicate that criminal sanctions still dominate judges' decisions in children in conflict with the law, and action sanctions are complementary sanctions because it is rarely applied.